Roles of lncRNAs in childhood cancer: Current landscape and future perspectives - Liu, Fei; Xiong, Qian-Wen; Wang, Jin-Hu; Peng, Wan-Xin (Frontiers in Oncology, 2023)
For children and adolescents, cancer is the leading cause of death. Approximately 400,000 children and adolescents between the ages of 0 and 19 are diagnosed with cancer each year worldwide. The cancer incidence rates have been rising for the past few decades. Generally, the prognosis of childhood cancers is favorable, but the survival rate for many unresectable or recurring cancers is substantially worse. Although random genetic mutations, persistent infections, and environmental factors may serve as contributing factors for many pediatric malignancies, the underlying mechanisms are yet unknown. Long non-coding RNAs (lncRNAs) are a group of transcripts with longer than 200 nucleotides that lack the coding capacity. However, increasing evidence indicates that lncRNAs play vital regulatory roles in cancer initiation and development in both adults and children. In particular, many lncRNAs are stable in cancer patients’ body fluids such as blood and urine, suggesting that they could be used as novel biomarkers. In support of this notion, lncRNAs have been identified in liquid biopsy samples from pediatric cancer patients. In this review, we look at the regulatory functions and underlying processes of lncRNAs in the initiation and progression of children cancer and discuss the potential of lncRNAs as biomarkers for early detection. We hope that this article will help researchers explore lncRNA functions and clinical applications in pediatric cancers.